2018
DOI: 10.1155/2018/6358949
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Element Numerical Investigation of Flow between Three Cylinders in an Equilateral‐Triangular Arrangement with Different Spacing Distances

Abstract: Two-dimensional incompressible Navier-Stokes equations are numerically solved using the high resolution spectral element method at Reynolds number 200. The flow between three cylinders in an equilateral-triangular arrangement is investigated. The center-to-center spacing distance ratio between two circular cylinders is varied from 1.5 to 12. Present numerical results show that the flow patterns and force characteristics are the result of the combined effects of Reynolds number, spacing distance, configuration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Furthermore, the power spectrum energy of both cylinders is almost the same which indicates the smooth passage of the fow in the down wake region. Bao et al [42] reported the single bluf body fow at g � 1.5 for the fow around three circular cylinders in the equilateral triangular arrangement. Rahman et al [43] also reported the single bluf body fow pattern for the fow behind two side-by-side square cylinders in the presence of a downstream control plate.…”
Section: Single Bluf Body Flowmentioning
confidence: 99%
“…Furthermore, the power spectrum energy of both cylinders is almost the same which indicates the smooth passage of the fow in the down wake region. Bao et al [42] reported the single bluf body fow at g � 1.5 for the fow around three circular cylinders in the equilateral triangular arrangement. Rahman et al [43] also reported the single bluf body fow pattern for the fow behind two side-by-side square cylinders in the presence of a downstream control plate.…”
Section: Single Bluf Body Flowmentioning
confidence: 99%